2013
DOI: 10.1111/aos.12325
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term results, prognostic factors and cataract surgery after diabetic vitrectomy: a 10‐year follow‐up study

Abstract: ABSTRACT.Purpose: To report long-term results, prognostic factors and cataract surgery after diabetic vitrectomy. Methods: Retrospective review of patient files from a large diabetes centre between 1996 and 2010. Surgical history was obtained from the Danish National Patient Register. Follow-up intervals were 3 months and 1, 3, 5 and 10 years after surgery. Results: In total, 167 patients had diabetic vitrectomy indicated for non-clearing vitreous haemorrhage (47%) and tractional retinal detachment (53%). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 21 publications
3
26
1
2
Order By: Relevance
“…Silicone oil was used in approximately 6% of cases, similar to some studies 11,12 but lower than the 23% rate reported by Ostri et al 13 Despite the higher tear rate in the delamination group, the postoperative retinal detachment rate was acceptable (2% in both groups), consistent with previous series (eTable in the Supplement). [11][12][13] Our VA analysis should be considered exploratory because, unlike the surgical complication data, VA data collection was not mandated, and not all hospitals used EMRs to record postoperative VA. Overall, 63% of eyes improved by at least 0.3 logMAR (approximately 2 Snellen lines) after surgery, with little difference between the eyes that underwent PPV with delamination and the eyes that underwent PPV without delamination.…”
Section: Discussionsupporting
confidence: 85%
“…Silicone oil was used in approximately 6% of cases, similar to some studies 11,12 but lower than the 23% rate reported by Ostri et al 13 Despite the higher tear rate in the delamination group, the postoperative retinal detachment rate was acceptable (2% in both groups), consistent with previous series (eTable in the Supplement). [11][12][13] Our VA analysis should be considered exploratory because, unlike the surgical complication data, VA data collection was not mandated, and not all hospitals used EMRs to record postoperative VA. Overall, 63% of eyes improved by at least 0.3 logMAR (approximately 2 Snellen lines) after surgery, with little difference between the eyes that underwent PPV with delamination and the eyes that underwent PPV without delamination.…”
Section: Discussionsupporting
confidence: 85%
“…We agree with Baun that the NPR currently is not a valid data source to monitor the PE risk, but this is largely due to non-compliance with the registration requirements mandated by law and to a much lesser degree with enjoyed reading the work of Ostri et al (2013) on long-term followup of patients with diabetic vitrectomy. The findings on cataract surgery are interesting, and I think some of my own data can add to the discussion regarding the requirement of cataract surgery, in particular, the effect of age and gas tamponade use on the development of cataract in this group of patients.…”
Section: Referencementioning
confidence: 61%
“…Tractional macular detachment remains one of the severe complications of PDR, and, even with successful surgery, visual recovery is often slow and may even take 1 year [10,22]. OCT imaging of the macular area can provide considerable help in explaining the mechanisms behind delayed functional recovery.…”
Section: Discussionmentioning
confidence: 99%
“…The results of surgical management of macula-off TRD depend on many factors, such as duration of macular detachment, timing of surgery, and extent of macular ischemia [8][9][10].…”
Section: Introductionmentioning
confidence: 99%